Projeto e análise de um biosensor plasmônico para medição de glicerol em aplicações point-of-care - Araújo, Magno Medeiros de (2023)
The manufacturing processes advancement in silicon wafers has enabled integration between electronics and photonics. Data will no longer be processed with electrons for the technology sectors but with photons, providing higher processing and transmission rates. In this context, the health and well-being sectors, for example, will have new equipment, allowing remote and individual monitoring and diagnosis, enhancing the prevention and treatment of diseases. Thus, this research proposes a photonic device with graphene applied and a surface plasmon resonance structure for sensing applications. Initially, they are concepts related to photonic devices and their different applications. Photonic crystals, plasmonic devices, graphene, and their use in optical guides are also presented. Then, the methodology used in the research development is explained, dealing with modeling and simulation. The results are presented and analyzed as the structure’s spectral behavior for different glycerol concentrations, which reinforces the potential for point-of-care applications considering its compactness and simplicity of construction